Benzylsulfonic acid functionalized mesoporous Zr-TMS catalysts: an efficient and recyclable catalyst for the preparation of coumarin derivatives by pechmann condensation reaction - Selvakumar, S.; Chidambaram, M.; Singh, A. P. (Catalysis Communications, 2007)
Benzylsulfonic acid functionalized mesoporous Zr-TMS (Zr-TMS-BSA, Zr-TMS, zirconia based transition metal oxide mesoporous molecular sieves) catalyst is used as an alternative to conventional acid catalysts in the von Pechmann condensation of aromatic alcohols with ethyl acetoacetate leading to the formation of coumarin derivatives in solvent free condition at 150 degrees C. Three types of coumarins, 7-hydroxy-4-methylcoumarin (beta-methylumbelliferone), 7-methoxy-4-methylcoumarin (Methyl-4-methylumbelliferyl ether) and 7,8-benzo-4-methylcoumarin derivatives have been prepared using resorcinol, 3-methoxyphenol and 1-naphthol, respectively. The catalytic activity and the recycle studies of the catalyst in all the three reactions proved the superior performance of the catalyst. Further the products were confirmed by GC, elemental analysis, melting point and NMR techniques. Finally, the probable mechanism for Pechmarm condensation using Zr-TMS-BSA catalyst has been reported. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzylsulfonic acid; Pechmann condensation and coumarins; Zr-TMS-BSA catalysts

Bridging the gap between micropores and mesopores by the controlled transformation of bifunctional periodic mesoporous silicas - Shylesh, S.; Srilakshini, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2008)
Novel bifunctional periodic mesoporous silicas having high content of organic groups in the pore channels and chromium in the frame wall has been synthesized by direct co-condensation method, using organo trialkoxysilanes (chloro propyl, vinyl, methyl), chromium nitrate and tetraethyl orthosilicate, in presence of cetyltrimethyl ammonium surfactants. The obtained materials show one main peak in the XRD patterns up to a molar ratio of 1: 1 between TEOS and organosilane in the synthesis gel and N-2 adsorption-desorption analysis shows that the mesopore structure remains intact after the surfactant removal process. Among the organosilanes, chloro propyl and vinyl pendant chromium samples shows a shift in the main peak to higher 2-theta values with a corresponding decrease in pore volume and pore diameter, with the percentage of organosilane functionalization. Small-pore silicas and chromium silicas can be prepared from the large pore mesoporous MCM-41, by effectively removing the organic groups by calcination. By this method, the pore size of the material can be tailored into the super-microporous region, without changing the chain length of the surfactant used in the assembly process. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups that the chloro propyl and vinyl pendant mesoporous materials show the maximum pore size shrinkage than the small chain length methyl units. Because of the tailorable pore size and with better textural characteristics, chromium-silica materials find applications in the field of shape selective heterogeneous catalysis, as demonstrated in the oxidation reaction of cyclohexane, than the conventional metal-containing mesoporous materials. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: bifunctional silicas; chromium; Cyclohexane; MCM-41; Oxidation

Benzoylation of anisole over silicotungstic acid modified mesoporous alumina - Selvakumar, S.; Singh, A. P. (Catalysis Letters, 2009)
Mesoporous alumina (MA) molecular sieves were synthesized by using aluminum sec-butoxide as Al precursor and lauric acid as the structure directing agent. The synthesized MA was functionalized with silicotungstic acid (STA) via wet impregnation method and characterized by various physico-chemical techniques. The XRD patterns of a series of HPA functionalized MA are showing the ordered structures. N(2) sorption analysis shows type IV isotherm. NH(3)-TPD measurements revealed an increase in number of acid sites with an increase in loading of STA over MA. At the same time decrease in the acidity was observed with the increase in calcination temperature of the supported materials. Functionalization of STA were also carried out over different alumina supports such as catapol-B (CB) and alumina synthesized without surfactant (ASW) and their activities were evaluated by carrying out liquid phase Friedel-Craft acylation (FC) reaction of anisole with p-toluoyl chloride in a batch reactor at 120 degrees C. Recycling was performed in the FC reaction using 30 wt% STA-MA two times and no major deactivation of the catalyst was observed.
Keywords: Friedel-Craft acylation; Mesoporous alumina; Silicotungstic acid

Binapthyl Schiff base diamine complex covalently bonded to modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Singh, A. P. (Catalysis Today, 2012)
Protected mesoporous SBA-15 phase was synthesized by grafting the complex Chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) through the reactive 3-aminopropyl trimethoxysilane(3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques like elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, XPS, and solid state C-13 NMR. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done for the oxidation reaction of thioanisole (methyl phenyl sulfide) using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and exhibit enantiomeric excess comparable to homogeneous catalyst. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: -OH protected NH2-SBA-15; Binaphthyl Schiff base ligand; Ordered mesoporous materials; Sulfoxidation; Thioanisole